Mesoporous additive-free vaterite CaCO3 crystals of untypical sizes: From submicron to Giant. (1st January 2021) - Vikulina, Anna; Webster, Joseph; Voronin, Denis; Ivanov, Evgenii; Fakhrullin, Rawil; Vinokurov, Vladimir; Volodkin, Dmitry
Abstract: Mesoporous CaCO3 crystals of sizes in the range 3–15 μm have attracted significant scientific attention as fully decomposable biocompatible drug delivery vectors. They are also used as sacrificial templates to produce polymer-based microcarriers (capsules, beads) and polymer scaffolds for tissue engineering at biologically friendly conditions. However, fabrication of CaCO3 crystals with the sizes beyond the conventional range without additives is still a challenge. There is a desperate need of sub-micrometre and sub-millimetre biocompatible and easily decomposable vectors for intracellular delivery and design of tailor-made polymer scaffolds, respectively. In this study, additive-free one-step fabrication of vaterite mesoporous crystals with sizes in the range from submicron (0.72 μm) up to tens of microns (55 μm) sizes is proposed. Crystals are grown by mixing of Ca 2+ and CO3 2− salts in aqueous media. Internal structure and morphology of the crystals have been investigated. Encapsulation of lysozyme by means of co-synthesis shows an enhanced entrapment into submicron crystals. Besides, the approach to grow CaCO3 crystals on the surface of microcellulose ьш is demonstrated opening broad avenues for the development of vaterite coatings technologies. Graphical abstract: Unlabelled Image Highlights: Nanocrystals of vaterite are synthetized in water without the use of additives >50 μm vaterite crystals are synthetized in water without the use of additives These crystals of different sizes have similar internal structure Stable coating of microfibrillar cellulose with vaterite crystals is obtained Loading capacity of nanocrystals is significantly higher than for large crystals